Functional integral approach to the transfer function of a stochastic scattering channel - Cabrera, Octavio; Zanette, Damian Horacio (Taylor & Francis, 2020)
Fil: Cabrera, Octavio Comisión Nacional de Energía Atómica. Instituto Balseiro; Universidad Nacional de Cuyo, Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas, Argentina